The Journals of Jeffery Amherst, 1757-1763, Volume 2 : A Dictionary of People, Places, and Ships - Andrews, Robert J., 1937- (Book collections on Project MUSE., 2015)
A Dictionary of People, Places, and Ships has more than 1,400 biographies of people mentioned by General Jeffery Amherst in his journals or identified by Robert J. Andrews in his notes. Included are entries for military and naval personnel, aboriginal leaders and warriors, and civilians. Where possible, a commission history is included for each officer of the French Forces, the Royal Navy, provincial officers, and regulars of the British Army. There is an extensive section about various types of commissions, ranks, units, regiments, and appointments. National origins of British army officers.